The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/celc.202001154
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Urchin‐Like CuWO4/WO3 Heterojunction Nanoarrays as Photoanodes for Photoelectrochemical Water Splitting

Abstract: With attractive visible‐light response and chemical stability, CuWO4 has emerged to be a promising candidate as a photoanode for photoelectrochemical (PEC) water oxidation. In this work, we report a one‐step hydrothermal method to prepare CuWO4‐based films directly grown on a conductive glass substrate from a stable precursor solution. By controlling the reaction duration, CuWO4/WO3 heterojunctions with urchin‐like nanoarray morphology are obtained. The CuWO4/WO3 film obtained with an optimized hydrothermal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…also reported that colloidal WO 3 nanowires for solar water splitting and it is reached 1.96 mA cm −2 at 1.23 V RHE under AM1.5G solar irradiation [47] . WO 3 based materials displayed enhanced photo/catalytic activities due to the increasing charge separation, stability and alleviate photogenerated holes accumulation on the surface [48–52] . Nonetheless, we believe that the overall catalytic activity of WO 3 NLs‐ITO in this study is somewhat limited due to the low content of catalyst on the electrode.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…also reported that colloidal WO 3 nanowires for solar water splitting and it is reached 1.96 mA cm −2 at 1.23 V RHE under AM1.5G solar irradiation [47] . WO 3 based materials displayed enhanced photo/catalytic activities due to the increasing charge separation, stability and alleviate photogenerated holes accumulation on the surface [48–52] . Nonetheless, we believe that the overall catalytic activity of WO 3 NLs‐ITO in this study is somewhat limited due to the low content of catalyst on the electrode.…”
Section: Resultsmentioning
confidence: 68%
“…[47] WO 3 based materials displayed enhanced photo/catalytic activities due to the increasing charge separation, stability and alleviate photogenerated holes accumulation on the surface. [48][49][50][51][52] Nonetheless, we believe that the overall catalytic activity of WO 3 NLs-ITO in this study is somewhat limited due to the low content of catalyst on the electrode. Our future studies will attempt to improve on these results through further fine-tuning of the BCP inclusion process for synthesising thicker and denser (in height and diameter) metal oxide structures.…”
Section: Chemelectrochemmentioning
confidence: 83%
“…[ 114–118 ] Hybridization of WO 3 with other semiconductors improves the separation of photo‐generated carriers and enhances the visible light absorption response. A variety of semiconductors have been coupled with WO 3 nanoarrays to form heterojunctions as improved photoanodes for water oxidation, including CuO (1.4 eV), [ 119 ] Fe 2 O 3 (2.0–2.2 eV), [ 115,120 ] SbSI (2.0 eV), [ 121 ] ZnIn 2 S 4 (2.0–2.4 eV), [ 122 ] CuWO 4 (2.25–2.45 eV), [ 116,123 ] BiVO 4 (2.4 eV), [ 54,124 ] CdS (2.4 eV) [ 125 ] and C 3 N 4 (2.7 eV). [ 126 ] The activities of some representative WO 3 ‐based heterojunction nanoarrays for PEC water splitting are summarized in Table 3 .…”
Section: Self‐supported Heterostructured Nanoarrays For Photoelectroc...mentioning
confidence: 99%
“…In addition to the increased carrier concentration noted by the above papers, Guo et al ascribed the improvement of PEC performance of CuWO 4 to the reduced activation energy of the water splitting reaction after the formation of oxygen vacancies on the surface of the photoanode . Different from doping and oxygen vacancies, constructing a heterojunction is a strategy for promoting the separation of photogenerated electron and hole pairs by forming a built-in electric field. The CuWO 4 /BiVO 4 type II heterojunction, CuWO 4 /Mn 3 O 4 p–n junction, and WO 3 /CuWO 4 heterojunction ,, were constructed, and a built-in electric field is formed because of the difference between the semiconductors. In addition, there are numerous studies to improve charge separation at the interface by loading cocatalysts on the surface.…”
Section: Introductionmentioning
confidence: 99%